2007
DOI: 10.1021/bi701142a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Folding and Unfolding Reactions of Single-Chain Monellin:  Evidence for Multiple Intermediates and Competing Pathways

Abstract: The mechanisms of folding and unfolding of the small plant protein monellin have been delineated in detail. For this study, a single-chain variant of the natively two-chain monellin, MNEI, was used, in which the C terminus of chain B was connected to the N terminus of chain A by a Gly-Phe linker. Equilibrium guanidine hydrochloride (GdnHCl)-induced unfolding experiments failed to detect any partially folded intermediate that is stable enough to be populated at equilibrium to a significant extent. Kinetic exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
192
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 46 publications
(206 citation statements)
references
References 68 publications
14
192
0
Order By: Relevance
“…This study has further brought out the complexity of the unfolding reaction by showing that the initially formed intermediate ensembles, I 1 and I 2 , unfold gradually, and not just in a few steps as indicated in the study in ref. 27. Here, it is shown that I 1 and I 2 possess native-like structure, as judged by the observation of only a very marginal loss in secondary structure at 150 ms of unfolding (Fig.…”
Section: Specific Structure Is Lost Gradually During the Unfolding Ofmentioning
confidence: 53%
See 4 more Smart Citations
“…This study has further brought out the complexity of the unfolding reaction by showing that the initially formed intermediate ensembles, I 1 and I 2 , unfold gradually, and not just in a few steps as indicated in the study in ref. 27. Here, it is shown that I 1 and I 2 possess native-like structure, as judged by the observation of only a very marginal loss in secondary structure at 150 ms of unfolding (Fig.…”
Section: Specific Structure Is Lost Gradually During the Unfolding Ofmentioning
confidence: 53%
“…In addition to WT MNEI (Cys42), 3 more mutant variants, C42AS68C (Cys68), C42AT82C (Cys82) and C42AP97C (Cys97), each with a single tryptophan residue (Trp4) and a single cysteine residue were generated by site-directed mutagenesis, and the proteins purified as described in ref. 27. The TNB-labeled proteins were obtained as described in SI Appendix.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations